METHODOLOGICAL APPROACHES TO ENSURING THE ECONOMIC SECURITY OF AN ENTERPRISE THROUGH INNOVATION AND INVESTMENT MECHANISMS (Development Service Industry Management, 2025)
The article considers the main methodological approaches to ensuring the economic security of an enterprise through the implementation of innovation and investment mechanisms. Particular attention is paid to the analysis of modern trends in the field of economic security, determining the role of innovation and investment processes in maintaining the stability of an enterprise and recommendations for increasing economic stability, competitiveness of enterprises and minimizing risks that may arise in the context of globalization and instability of market conditions.An innovative and investment mechanism for ensuring the economic security of an enterprise has been developed, which includes a set of means, methods, tools and procedures necessary for designing its elements in the context of implementing innovative products or new production processes using investment resources. As a result of its implementation, it is expected to form an effective system of elements capable of ensuring a stable level of economic security of the enterprise. At the same time, although the methods and tools of this subsystem remain unchanged, their order of interaction, functional purpose and management mechanisms undergo transformations.To achieve the effectiveness of the development of an effective innovation and investment mechanism, it was proposed to use components that allow not only to analyze the current state of the enterprise's economic security, but also to predict changes in the indicators of the innovation and investment components based on the data obtained. The components of the mechanism for ensuring the economic security of the enterprise represent a closed-loop system. This means that its functioning is carried out continuously and in a mode of constant monitoring, adapting to the changing conditions of the external and internal environment. Thanks to this closed system, all stages of ensuring economic security - from forecasting threats to their prevention and minimization - are not just interconnected, but also self-supporting through constant feedback to new challenges and changes. This approach makes it possible to provide more accurate forecasting and the optimal ratio of innovation and investment costs in the context of ensuring economic security, and also allows for timely adjustments to strategic decisions in the event of new threats or opportunities. A detailed distinction was made between the components of such a mechanism that ensures the economic security of the enterprise.
Keywords: methodological approaches; economic security; innovation and investment mechanism; enterprise; innovation; investment; mechanism; competitiveness; tasks; methods; tools